The impact of women's presence on the board of directors on capital structure and company failure risk - Fajri Rezano Pangestu Aji; Doddy Setiawan (Jurnal Manajemen dan Pemasaran Jasa, 2022)
This paper examines the relationship between the presence of women on the board of directors to capital structure and the risk of company failure. This study divides capital structure decisions into three measurements, namely Leverage, Maturity or also known as Debt Maturity, and Cost of Debt. For leverage and Maturity, we do not find a significant relationship with women on the board of directors. We use the annual financial data of Trade, Services, and Investment service sector companies recorded on the IDX for two years of research, which are the data for 2018 and 2019. Our paper yields two main findings. First of all, the relationship between women on the board of directors and the risk of company failure is negative and significant. These outcomes can be explained by Agency Theory which considers that through transformational leadership, women pay attention to the interests of others and build positive relationships with colleagues and employees by eliminating information asymmetry. Thus, the company's performance can be maintained and avoid the risk of failure. Second, we reveal that there is a negative and significant influence among women on the board of directors on the cost of debt. Companies led by female directors tend to minimize debt so that debt financing will be lower than total assets. Low debt financing will reduce the company's cost of debt.